Discovering compassion in medical training: a qualitative study with curriculum leaders, educators, and learners - Lane, Charles B.; Brauer, Erin; Mascaro, Jennifer S. (Frontiers in Psychology, 2023)
Background: Compassion is considered a fundamental human capacity responsible for the creation of medicine and patient-centered innovation in healthcare. However, instead of nurturing and cultivating institutional compassion, the health system itself is considered a direct barrier to standard care. This trend of compassion depletion extends to medical students and the culture of undergraduate medical training, while rates of student depression, substance use, and suicidality increase sharply during education. Objectives: The goal of this qualitative study is to develop a more comprehensive understanding of compassion as it relates to undergraduate medical education. Focus groups with key stakeholders in medical education probed beliefs about the nature of compassion as well as to identify perceived barriers and hindrances to compassion within the daily responsibilities of educators and students. Methods: Researchers conducted a series of virtual (Zoom) focus groups with key stakeholders: Students (N=14), Small Group Advisors (N=11), and Medical Curriculum Leaders (N=4). Anonymous transcripts were thematically analyzed using MAXQDA software. Results: Study participants described compassion as more than empathy, demanding action, and capable of being cultivated. Stakeholders identified self-care, life experiences, and role models as facilitators, and time constraints, culture, and burnout as barriers to compassion. Both medical students and those training them agreed about what compassion is and that there are ways to cultivate more of it in their daily professional lives. They also agreed that undergraduate medical education – and the healthcare culture at large – does not deliberately foster compassion, and indeed may be directly contributing to its degradation by the content and pedagogies emphasized, the high rates of burnout and futility, and the overwhelming time constraints. Conclusions: Intentional instruction in and cultivation of compassion during undergraduate medical education could provide a critical first step for undergirding the professional culture of healthcare with more resilience and warm-hearted concern. Our finding that medical students and those training them agree about what compassion is and that there are specific and actionable ways to cultivate more of it in their professional lives highlights key changes that will promote a more compassionate training environment conducive to the experience and expression of compassion.